11th Arctic Ungulate Conference (AUC) - Nieminen, Mauri (Rangifer, 2005)
The 11th Arctic Ungulate Conference (AUC) wasorganised by the Finnish Game and Fisheries Research Institute (RKTL) in Saariselkä, in the Heart of Lapland, Finland, 24-28 August 2003. The conference continued a series of ten conferences devoted to Arctic Ungulates, including five Reindeer/Caribou Symposia, two Muskox Symposia and three Arctic Ungulate Conferences. The series began with the 1st International Reindeer/Caribou Symposium held in Fairbanks, Alaska, in 1972